2004
DOI: 10.1088/0031-8949/70/2-3/010
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of Electron Angular Distribution in Resonant Auger Decay for Na, Ba, Hg and Kr

Abstract: The angular anisotropy parameters of the Auger decay α2 and spin polarization parameters β2 were calculated for Na, Kr, Xe, Ba, and Hg using the multichannel Dirac–Fock method. These calculations were performed using LSJ and relativistic intermediate coupling. The exchange effect was used in all calculations. We showed numerically that orbital relaxation during the Auger decay had only a small effect on the angular distribution for open-shell atoms. The obtained values for α2 and β2 were compared with other th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…Again, these two data sets have been obtained by accounting for orbital relaxation during the Auger decay. Elizarov and Tupitsyn did not investigate this discrepancy any further [10], they only suggested that the discrepancy may have something to do with the phase differences which are 'not the same as those presented in table 2' of our work [5]. They neither give any values for their phase differences nor do they give any information on how much their phase differences deviate from ours.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…Again, these two data sets have been obtained by accounting for orbital relaxation during the Auger decay. Elizarov and Tupitsyn did not investigate this discrepancy any further [10], they only suggested that the discrepancy may have something to do with the phase differences which are 'not the same as those presented in table 2' of our work [5]. They neither give any values for their phase differences nor do they give any information on how much their phase differences deviate from ours.…”
mentioning
confidence: 58%
“…For the remainder of the comment we will leave any data obtained in the frozen-core approximation out and focus on Elizarov and Tupitsyn's realization that there is a huge discrepancy between their [10,11] and our [5] results for the angular anisotropy parameter α 2 for the L 3 M 1 M 4,5 Auger transitions of Kr, Xe, Ba, and Hg, see columns a and c of table 1. Again, these two data sets have been obtained by accounting for orbital relaxation during the Auger decay.…”
mentioning
confidence: 92%
See 3 more Smart Citations